2012
DOI: 10.4158/ep12072.or
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors Ofvitamin D Deficiency in Healthy Adults

Abstract: Objective Vitamin D deficiency is highly prevalent in high-risk patient populations, but the prevalence among otherwise healthy adults is less well-defined. The goal of this study was to determine the prevalence and predictors of low 25-hydroxyvitamin D [25(OH)D] levels in healthy younger adults. Methods This was a cross-sectional study of 634 healthy volunteers aged 18-50 years performed between January, 2006 and May, 2008. We measured serum 25(OH) D and parathyroid hormone and recorded demographic variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 40 publications
8
70
2
Order By: Relevance
“…When the prevalence of each category reported by each of these six studies were weighted for sample size and subsequently averaged, 27.7 % were vitamin D deficient, 38.4 % were insufficient, and 33.8 % were replete. This overall prevalence of vitamin D deficiency was slightly lower than what has been reported for the general population of childbearing age women in the US (31 %) [3]. As Vanni et al [80] reported, a lower prevalence of vitamin D deficiency is to be expected in a population of women seeking IVF, as these women tend to have higher socioeconomic status as well as education level, both of which are factors associated with higher vitamin D levels.…”
Section: Vitamin D Deficiency Prevalencementioning
confidence: 59%
See 3 more Smart Citations
“…When the prevalence of each category reported by each of these six studies were weighted for sample size and subsequently averaged, 27.7 % were vitamin D deficient, 38.4 % were insufficient, and 33.8 % were replete. This overall prevalence of vitamin D deficiency was slightly lower than what has been reported for the general population of childbearing age women in the US (31 %) [3]. As Vanni et al [80] reported, a lower prevalence of vitamin D deficiency is to be expected in a population of women seeking IVF, as these women tend to have higher socioeconomic status as well as education level, both of which are factors associated with higher vitamin D levels.…”
Section: Vitamin D Deficiency Prevalencementioning
confidence: 59%
“…Mitchell et al [3] reported the incidence of vitamin D deficiency (defined as <20 ng/mL) in reproductive age females to be 31 %. Data from the National Health and Nutrition Examination Surveys (NHANES) [4] found that risk varied between racial and ethnic groups, with non-Hispanic blacks demonstrating a higher prevalence of vitamin D deficiency and inadequacy as compared to their white counterparts.…”
Section: Epidemiology Of Vitamin D Deficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…It is needed by genes/cells that express mucin (a polysaccharide) of major importance in one of the three major tear layers. Vitamin D 3 , a fat soluble vitamin that is generally deficient in the American diet, is also incorporated [22]. Numerous clinical studies have elucidated the health benefits of vitamin D and many are likely explained by its master effects on immunity and systemic inflammation [23].…”
Section: Discussionmentioning
confidence: 99%